ANTI-CORRUPTION RESPONSIBILITIES OF CANDIDATES ACCORDING TO THE LEGISLATION OF KAZAKHSTAN (based on materials of the election campaign for the elections of the Mazhilis of Kazakhstan 2023) - Makartsev Андрей Алексеевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article notes that the institution of elections is one of the important elements of state security in any state. In this regard, it is common practice to enshrine in national electoral legislation provisions aimed at ensuring law and order in various spheres of life. Anti-corruption norms occupy a special place in electoral legislation. The article notes that the institution of elections is one of the important elements of state security in any state. In this regard, it is common practice to enshrine in national electoral legislation provisions aimed at ensuring law and order in various spheres of life. Anti-corruption norms occupy a special place in electoral legislation. According to the author, the enshrinement of anti-corruption responsibilities in the electoral legislation is connected to a greater extent not with electoral law, but with the legislation defining the legal status of deputies and elected officials. The author examines the features of establishing anti-corruption responsibilities in the legislation of the Republic of Kazakhstan, as well as electoral practice. In most cases, the judicial authorities decided to uphold the decision of the relevant election commission to cancel the registration of a candidate. Moreover, in a number of cases, candidates managed to overturn the decision of the election commission to refuse registration. An analysis of electoral practice led to the conclusion that in most cases, many offenses in the area under consideration were the result of candidates’ legal illiteracy, their inattention, and the amount of unreliable information was most often insignificant. In this regard, it is concluded that the legislation should allow election commissions and judicial bodies to more widely use their own discretion when resolving such cases.